Emília Amor. Didática do Português. Sinais de um Percurso de Vida, Vila Nova de Gaia: Fundação Manuel Leão, 2022. 208 pp. ISBN 978-989-8151-63-6. - Correia, Miguel (Linguarum Arena, 2024)
DOI: https://doi.org/10.21747/1647-8770/are14r1